Cystoid Macular Edema 18 Years after Anterior Chamber Phakic Intraocular Lens Implantation - Elias L. Warrak; Majd S. Haddam; Walid N. Dandan; John E. Warrak; Fady K. Sammouh (Case Reports in Ophthalmological Medicine)
We report a case of a 54-year-old female patient who underwent PAC-IOL implantation 18 years prior to presentation. The patient had a best corrected visual acuity (BCVA) 20/20 in the right eye (OD) postoperatively with normal eye exam on routine follow-up since then. The patient presented for acute onset decreased visual acuity in the right eye. BCVA was 20/60, and exam showed blunted macular reflex with no evidence of inflammation. Optical coherence tomography (OCT) showed CME. She was started on topical treatment (ketorolac 0.5%) OD four times daily. Three weeks later, the patient had a BCVA of 20/20 OD with a normal macular reflex and an OCT showing the resolution of the CME. To our knowledge, this is the first reported case of a CME 18 years post PAC-IOL implantation. The possible cause of this incidence could be related to subclinical intraocular inflammation. Ophthalmologists should be aware of the possibility of such a latent CME post-PAC-IOL implantation.